Analisis Keandalan Data Penakar Hujan Otomatis Sebagai Acuan Koreksi Perkiraan Hujan Radar - Roby Hambali; Djoko Legono; Rachmad Jayadi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
The reliability test of automatic rain gauge data in the Mt. Merapi region is highly needed considering that the data is used as a reference to correct the X-band MP radar rainfall estimates error. Rain gauge stations containing unreliable data need to be eliminated so that radar rainfall estimates can be adjusted based on reliable data only. This paper discusses the technique of examining the reliability of rain gauge data using a two-way analysis of variance. The method used in variance analyzing is the Scheffe test, where the difference in the mean value of the two rain gauge stations is compared with the critical value of the Scheffe test. The criteria appointed to declare 'reliable' is if the number of stations that have a significant difference with the reviewed station is less than two. A total of 5939 10-minute rainfall intensity data from 21 rain gauge stations in the Mt. Merapi region were used in the analysis. The results show that six of the 21 rain gauge stations contain unreliable data to use as a reference for correcting radar rainfall estimates. The Scheffe test is considered excellent and straightforward to apply to find out the variance of mean values between rain gauge stations.